Empirical likelihood and quantile methods for time series : efficiency, robustness, optimality, and prediction /: efficiency, robustness, optimality, and prediction. ([2018]) - Liu, Yan; Akashi, Fumiya; Taniguchi, Masanobu
No abstract available